Age at childhood infections and risk of atopy - Bager, P (BMJ Group, 2002)
Background: It has been proposed that early age at exposure to common childhood infections is associated with a decreased risk of allergy. Previous studies on the possible association between allergy and infection with measles, mumps, rubella, and varicella have not been conclusive as most did not include information on exact age at exposure. The objective of our study was to investigate whether early age at exposure to these infections was associated with a decreased risk of atopy using information on exact age at infection. Methods: The study population consisted of 889 pregnant women who participated in a national birth cohort study in Denmark and for whom detailed information on history of measles, rubella, varicella, and mumps before school entry (age 7 years) was available from school health records from Copenhagen. Atopic status was assessed serologically by a specific response to 11 common inhalant allergens using serum samples obtained from the women during pregnancy. Results: Measles in the first year of life was associated with a higher risk of atopy than no measles before age 7 years (OR 3.36, 95% CI 1.47 to 7.68). There was no association between atopy and mumps, rubella, or varicella in the first 7 years of life or with measles acquired after the first year of life. The risk of atopy increased significantly with increasing number of childhood infections in the first 2 years of life (p(trend)=0.01). Conclusions: These findings do not support the suggestion that childhood exposure to measles, rubella, varicella, or mumps protects against atopy, even if acquired very early in life.